Long-Term Survival of More than 5 Years with Maintenance Therapy Using Single-Agent Pemetrexed in a Patient with Diffuse Malignant Peritoneal Mesothelioma - Yasuo Otsuka; Yoriaki Komeda; Masayuki Takeda; Takayuki Takahama; Masashi Kono; Mamoru Takenaka; Satoru Hagiwara; Naoshi Nishida; Hiroshi Kashida; Masatoshi Kudo (Case Reports in Medicine)
A 76-year-old woman presented with lower abdominal pain and nausea and was referred to the gastroenterology department in our institution. Previous contrast-enhanced computed tomography (CE-CT) for follow-up after breast cancer surgery had indicated a soft tissue mass below the right diaphragm, which was considered a benign change. CE-CT performed at the first visit to our department revealed further thickening of the soft tissue mass with extension to the liver surface. In addition, ascites and nodules were observed in the abdominal cavity. Histopathological examination of a biopsy specimen revealed peritoneal invasion of atypical epithelioid cells with trabecular and glandular patterns. The tumor cells were positive for AE1/AE2, calretinin, WT-1, D2-40, HEG1, EMA, BAP1, and MTAP and negative for carcinoembryonic antigen, MOC-31, Ber-Ep4, ER, PgR, TTF-1, claudin 4, and desmin. A diagnosis of epithelioid mesothelioma was made. The patient received chemotherapy with cisplatin (75 mg/m2) and pemetrexed (500 mg/m2). After six courses of combined chemotherapy, pemetrexed was administered as a single agent. At the time of writing this report, she was undergoing over the 30th course of chemotherapy without any significant side effects. Diffuse malignant peritoneal mesothelioma is a rare, fatal, and progressive disease. Our patient achieved long-term survival of more than 5 years with maintenance therapy using single-agent pemetrexed.